Data on the effect of co-fermentation of maize and leguminous crops on biogas production, methane production and methane content in biogas - Kintl, Antonín; Huňady, Igor; Sobotková, Julie; Vítěz, Tomáš; Brtnický, Martin; Vejražka, Karel; Elbl, Jakub (Data in brief, 2024)
The presented set of data brings results of the experimental production of biogas and methane from silages of alternative substrates consisting of maize and three leguminous species with a potential to make the production of biogas more friendly to the environment because the cultivation of legumes is generally considered to be more environment friendly than the cultivation of maize: white sweet clover (Melilotus albus Medik.), fodder vetch (Vicia villosa Roth.) and white lupin (Lupinus albus L.). Obtained data allow to compare the composition of experimental substrates and their important parameters (VS, DM, NDF, ADF, CF, starch, cellulose, hemicellulose, CP, lipids and ADL) as well as the yield of biogas, methane and methane in biogas from silage produced as a monosubstrate from the biomass of maize shreddings on the one side with silages produced from the mixture of biomass from maize and diverse legumes on the other side. This set of data can contribute to awareness about possibilities for reducing environmental risks connected with the cultivation of maize in growers of energy crops and operators of biogas plants. The reason is that a considerable number of farmers do not use new technologies of growing biomass for the production of biogas as they cannot quantify the potential impact on biogas yield and hence on the profitability of biogas plant operation. The measured values demonstrate that silages made from the mixed culture were reaching at least the same production of biogas and its quality as the monocultural maize silage.
Keywords: Cropping system; Legumes; Methane yield; Biomass; Silage; Biogas; Anaerobic digestion